1983
DOI: 10.1139/v83-313
|View full text |Cite
|
Sign up to set email alerts
|

The stationary-state approximation in the photolysis of acetone

Abstract: A mechanism has been written for the photolysis of acetone at 313 nm and 253.7 nm and the differential equations involved solved rigorously. Testing this mechanism has revealed inconsistencies between different sets of experiments that were not previously obvious. The stationary-state approximation is valid up to ca. 0.5% decomposition but its practical usefulness is minimal. Graphs are given showing the variation of all significant quantum yields with temperature, pressure, and light intensity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…This behavior would be difficult to reconcile with the pressure quenching observed for the CH 3 CO quantum yield, unless the breakup of CH 3 CO* toward CH 3 and CO is assisted by collisions. Evidence for this process has been obtained in the 313 nm photolysis of acetone and the model calculations of Nicholson …”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…This behavior would be difficult to reconcile with the pressure quenching observed for the CH 3 CO quantum yield, unless the breakup of CH 3 CO* toward CH 3 and CO is assisted by collisions. Evidence for this process has been obtained in the 313 nm photolysis of acetone and the model calculations of Nicholson …”
Section: Discussionmentioning
confidence: 90%
“…Similar mechanisms have been discussed in earlier studies. 6,7,12,13,16 Fluorescence from the excited singlet state has a low probability and is neglected here. However, internal energy conversion induced by collisions, process e, is included because Gandini and Hackett 16 had found that intersystem crossing is accelerated by increasing the pressure of CO 2 , which they used as an inert quenching gas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acetone is among the organic compounds identified as hazardous air and industrial wastewater pollutants. Acetone photochemistry has been studied by many workers (11)(12)(13)(14)(15)(16)(17) in the pure liquid as well in the gas phase for over 50 years, but only a few reports on its decomposition by UV light irradiation in dilute aqueous solution exist (18)(19)(20). Acetone is not only a weak absorber but also degrades very slowly by direct photolysis [quantum yield of 0.061 at 270 ( 2.5 nm (19)].…”
Section: For Examplementioning
confidence: 99%
“…It seems fundamental to study QSSA in the rigorous frame of reversible elementary reactions because it is the cornerstone for reducing the chemical mechanisms of complex systems (6 ). A great number of papers deal with QSSA applied to complex systems, owing to the importance of this approximation in chemical kinetics (7)(8)(9)(10)(11)(12)(13)(14). In most cases the same kinetic system has been simulated with and without the application of QSSA and the results have been compared as noted by Turanyi (15).…”
mentioning
confidence: 99%